2019
DOI: 10.15605/jafes.034.01.08
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Patient Decision Aid on the Choice of Diabetes Medication for Filipino Patients with Type 2 Diabetes Mellitus

Abstract: Objective. To develop a locally adapted patient decision aid (PtDA) on treatment intensification among Filipino patients with Type 2 Diabetes Mellitus and to test the feasibility of using PtDAs in a low middle-income country Methodology. A qualitative approach and an iterative process of development of a PtDA were employed for this study. We describe the process of developing a Filipino version of the Diabetes Medication Decision Aid. This PtDA was designed to help the patient choose the appropriate treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
(67 reference statements)
1
1
0
Order By: Relevance
“…This finding is of great importance to the evidence base for SDM and decision aids in general since most studies on the subject are conducted in Western countries. This finding is also consistent with the finding of a previously published study on the use of a decision aid in the Filipino population [17].…”
Section: Principal Findingssupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is of great importance to the evidence base for SDM and decision aids in general since most studies on the subject are conducted in Western countries. This finding is also consistent with the finding of a previously published study on the use of a decision aid in the Filipino population [17].…”
Section: Principal Findingssupporting
confidence: 92%
“…Nevertheless, it has been found that patients in Asia want to be involved in SDM [15,16]. In the Philippines, there has only been one published study on a PDA that was developed for diabetic patients choosing an oral hypoglycemic agent [17]. This study found that PDAs are feasible to use in a lower middle-income country without significantly increasing consult time.…”
Section: Introductionmentioning
confidence: 96%